DISTRIBUSI DAN DETERMINAN HIPERTENSI DI KECAMATAN SAMBIREJO, KABUPATEN SRAGEN - Pariawan Lutfi Ghazali (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: One of the most prevalent degenerative diseases is hypertension. The statistic data of Sambirejo sub-district of Sragen Regency shows that hypertension is the disease with the second largest number of patients. Research on the distribution and determinant of hypertension needs to be done to support intervention efforts.Objective: This study aims to determine the distribution and determinants of hypertension in Sambirejo sub-district, Sragen Regency.Methods: This observational study used a cross-sectional design, with descriptive analytic types. The sample was taken using a stratified random sampling technique. Blood pressure measurements using sphygmomanometer, and other data obtained from questionnaires and direct measurements. We tested the relationship between variables with Kruskal-Wallis bivariate analysis. The multivariate analysis used is Ordinal Regression. Data were statistically significant if p <0.05 (CI: 95%).Results: The study sample was 454 people. Respondents who experienced hypertension were very high at 57.2%. Hypertension is more prevalent in men, and ages 40 and above. Determinant factors of hypertension are age, gender, genetics, exercise habits, smoking habits, fruit and vegetable consumption, and body mass index. Multivariate analysis with ordinal regression test showed the factors to influence the hypertension were genetic factors (OR=4,777; 95% CI 3,232-7,059; p=0,000), smoking (OR=1,004, 95%CI: 1,003 – 1,004, p=0,0001), and body mass index. (OR=1,054; 95%CI:1,002 – 1,109, p=0,042).Conclusion: Hypertension distribution is more dominant in the male group, and =40 years of age. Determinants of hypertension are age, sex, genetics, exercise habits, smoking habits, fruit and vegetable consumption, and body mass index. Genetic factors are the dominant determinant for hypertention.